Searching for ethical leadership in nursing - Makaroff, Kara Schick (Nursing ethics, 2014)
Background:Attention to ethical leadership in nursing has diminished over the past several decades.Objectives:The aim of our study was to investigate how frontline nurses and formal nurse leaders envision ethical nursing leadership.Research design:Meta-ethnography was used to guide our analysis and synthesis of four studies that explored the notion of ethical nursing leadership.Participants and research context:These four original studies were conducted from 1999-2008 in Canada with 601 participants.Ethical considerations:Ethical approval from the original studies covered future analysis.Findings:Using the analytic strategy of lines-of-argument, we found that 1) ethical nursing leadership must be responsive to practitioners and to the contextual system in which they and formal nurse leaders work, and 2) ethical nursing leadership requires receiving and providing support to increase the capacity to practice and discuss ethics in the day-to-day.Discussion and conclusion:Formal nurse leaders play a critical, yet often neglected role, in providing ethical leadership and supporting ethical nursing practice at the point of patient care.